(untitled) (Research, Society and Development, 2021)
Joining the medical course brings students the responsibility to acquire knowledge about self-care, enlightening and behavior of patients about STIs (Sexually Transmitted Infections). This study aimed to analyze the objective knowledge of medical students about the transmission, manifestations, treatment and prevention of STIs, analyze the sexual behavior of medical students in relation to self-care to prevent STIs and analyze the adherence of medical students to forms of STI prevention. This is a descriptive quantitative cross-sectional paper based on a questionnaire applied to 125 students. The results showed acceptable knowledge from the students, greater variety of sexual partners in males and a higher rate of satisfactory vaccination for HPV (Human Papilloma Virus) in females. The findings show satisfactory knowledge, risky behaviors and poor adherence to forms of prevention by students against STIs.